STRATEGIES FOR HOUSING AFFORDABILITY IN NIGERIA - Oluwaseyi AJAYI; Oluranti AJAYI; Olusegun AKINSIKU; Temidayo OSUNSANMI (Journal of Construction Project Management and Innovation, 2016)
Population in urban areas are growing at a rapid rate, thus recycling of land becomes necessary despite that fact that land is a finite resource. The gap between supply and demand for housing is an issue for the government to address in order to provide housing at a cheaper rate which is the basic need of man. The purpose of this study is to assess the strategies for affordable housing in Nigeria. Research design was used and the population of the study was Architects, Quantity Surveyors, Engineers, Contractors and project managers. Random sampling technique was adopted for this study. A total of 70 questionnaires were distributed and 51 were returned. This represents a response rate of 73%. Statistical Package for Social Sciences (SPSS) was used for analysis via descriptive and inferential statistics. The study showed that problem of land inaccessibility, stunted financial and mortgage system were the factors affecting housing delivery. Challenges of housing delivery were high cost of acquiring land, social miscreants (“Omo Onile”) and affordability. Anti-corruption measures and a responsive judiciary, Cost – saving house design, Land reforms/reviews of land use act and review of fiscal and monetary  policies to reduce inflation and interest rate were the strategies to be used to ensure affordable housing. In conclusion, the Government should create an enabling environment for private sector by reducing the interest rate, taxes collected and creation of a viable housing mortgage sector to cater for the need of interested mortgage loan applicants. The use of the land should be constrained to affordable housing.